A qualitative study investigating students’ perception on cluster school teachers’ quality - Anamala, Gaytri; Abd Rahman, Fadzilah; Said, Rozita Radhiah (Global Business Entreprenueurship, 2017)
Quality of cluster school teachers is the mechanism to influence students’ achievement. Teachers possessing good qualities will positively impact teaching and learning in the classroom. Therefore, the purpose of this study is to investigate students’ perception on cluster school teachers’ quality as outlined in Model Standard Guru Malaysia (SGM). Students’ perception is assessed based on the type of qualities displayed by teachers and the importance of quality teachers’ to students. Qualitative research using partial structured interviews using form 5 students that has a high, medium and lower performance from the cluster school in the District of Johor Bahru used as samples. The findings show that teachers had most of the features qualities outlined in the Model Standard Guru Malaysia (SGM). However, there are some features of qualities that still need to be improved by teachers to become teacher with the highest quality. Quality teachers’ are also found to be very important because each teacher observed and emulated by pupils in order to become an excellence human capital.